Public Sector Accounting: A Key to Achieving the Sustainable Development Goals (SDGs) - Sapa’, Angela Batara; Haliah, Haliah; Kusumawati, Andi (Asian Journal of Applied Business and Management, 2024)
This study aims to explore the role of public sector accounting in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia. Public sector accounting plays a key role in ensuring transparency, accountability, and efficiency in the sustainable management of government finances. This study employs a qualitative method with a literature review approach, examining various research and reports related to the implementation of accrual-based accounting, the Balanced Scorecard (BSC), and sustainable finance. The findings indicate that the implementation of accrual-based Government Accounting Standards (SAP) has improved the quality of local government financial reports, positively impacting public financial governance. Additionally, the use of BSC in performance-based budgeting is deemed capable of supporting the achievement of the SDGs pillars, particularly in the education, health, and economic sectors.